The Complete Works of Artemus Ward $1 (BPart 6: Artemus Ward's Panoramas - Ward, Artemus, 1834-1867 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Complete Works of Artemus Ward $1 (BPart 6: Artemus Ward's Panorama" by Ward is a humorous collection written during the mid-19th century, specifically in a period characterized by literary revival and social satire. This book is a compilation of lectures that showcase the wit and observations of the author, Charles Farrar Browne, as he performs his unique brand of comedy. The likely topic of the book revolves around the life and culture of Mormons in the American West as seen through the eyes of a humorist, providing a blend of comedic narrative and social commentary. In this part of his complete works, Artemus Ward presents a series of lectures known as "Artemus Ward's Panorama," where he humorously recounts his travels and experiences among the Mormons in Utah. The content centers on his observations of Mormon society, including their customs, personalities, and the larger-than-life figure of Brigham Young, all interspersed with comedic anecdotes, clever irony, and social critique. Ward engages the audience with his witty remarks on the peculiarities of life in Utah, the challenges of his travels, and the often absurd aspects of the Mormon lifestyle, all while using the backdrop of a panorama to illustrate his points in an entertaining and engaging manner. The lectures paint a rich picture of the era's cultural landscape, emphasizing both the humor and human interest in the lives of the people he encountered. (This is an automatically generated summary.)s
Release date is 2002-06-01
This etext was produced by anonymous Project Gutenberg Volunteers
Keywords: American wit and humor